Protective effect of UDCA against IL-11- induced cardiac fibrosis is mediated by TGR5 signalling - B. Reilly-O’Donnell; E. Ferraro; R. Tikhomirov; R. Nunez-Toldra; A. Shchendrygina; L. Patel; Y. Wu; A. L. Mitchell; A. Endo; L. Adorini; R. A. Chowdhury; P. K. Srivastava; et al. (Frontiers in Cardiovascular Medicine, 2024)
IntroductionCardiac fibrosis occurs in a wide range of cardiac diseases and is characterised by the transdifferentiation of cardiac fibroblasts into myofibroblasts these cells produce large quantities of extracellular matrix, resulting in myocardial scar. The profibrotic process is multi-factorial, meaning identification of effective treatments has been limited. The antifibrotic effect of the bile acid ursodeoxycholic acid (UDCA) is established in cases of liver fibrosis however its mechanism and role in cardiac fibrosis is less well understood.MethodsIn this study, we used cellular models of cardiac fibrosis and living myocardial slices to characterise the macroscopic and cellular responses of the myocardium to UDCA treatment. We complemented this approach by conducting RNA-seq on cardiac fibroblasts isolated from dilated cardiomyopathy patients. This allowed us to gain insights into the mechanism of action and explore whether the IL-11 and TGFβ/WWP2 profibrotic networks are influenced by UDCA. Finally, we used fibroblasts from a TGR5 KO mouse to confirm the mechanism of action.Results and discussionWe found that UDCA reduced myofibroblast markers in rat and human fibroblasts and in living myocardial slices, indicating its antifibrotic action. Furthermore, we demonstrated that the treatment of UDCA successfully reversed the profibrotic IL-11 and TGFβ/WWP2 gene networks. We also show that TGR5 is the most highly expressed UDCA receptor in cardiac fibroblasts. Utilising cells isolated from a TGR5 knock-out mouse, we identified that the antifibrotic effect of UDCA is attenuated in the KO fibroblasts. This study combines cellular studies with RNA-seq and state-of-the-art living myocardial slices to offer new perspectives on cardiac fibrosis. Our data confirm that TGR5 agonists, such as UDCA, offer a unique pathway of action for the treatment of cardiac fibrosis. Medicines for cardiac fibrosis have been slow to clinic and have the potential to be used in the treatment of multiple cardiac diseases. UDCA is well tolerated in the treatment of other diseases, indicating it is an excellent candidate for further in-human trials.